Stylistics: Towards a Linguistic Analysis of Literature - Mytha Candria (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
A linguistic analysis of literature has caused debates among linguists and between linguists and literary critics. The debate among linguists occurs because they have different opinions regarding the nature of literary language, while the debate between linguists and literary scholars arises as literary scholars question the authority of linguistics to study literary writings. Therefore, in this paper I argue that the language of literature is similar to that of non-literary texts, and I also believe that because the centrality of language in literary writings, linguistics, as the study of language, has the authority to study literature. One linguistic approach to literature is stylistics, which studies the forms, functions, and meanings of literary language in a detailed and systematic way. Keywords: linguistics; literature; literary language; stylistics;